PERAN GUIDED INQUIRY DALAM PEMAHAMAN KONSEP SISWA KELAS VIII PADA PEMBELAJARAN TEOREMA PYTHAGORAS - Oktinasari, Hanifah; Prahmana, Rully Charitas Indra (Universitas Papua, 2020)
This study aims to determine the role of Guided Inquiry in understanding students' concepts in learning the Pythagorean theorem, through student worksheet-based guided inquiry learning models. This study uses descriptive qualitative research methods, which were carried out in class VIII D at SMP Muhammadiyah 1 Gamping. Data collection techniques used were documentation, observation, and written tests. Data obtained in this study were analyzed using data triangulation techniques. The results showed that the Guided Inquiry had a role in helping students to understand the concept of the Pythagorean theorem formula, through several stages of learning. In learning that uses guided inquiry, students can understand the Pythagorean theorem formula by finding it on their own and being facilitated by the teacher. Also, student learning outcomes indicate that the average value obtained by students is above the Minimum Mastery Criteria score for mathematics subjects of 65.